INTERPRETASI HUKUM ISLAM DAN HUKUM POSITIF TERHADAP TINDAKAN POLIGAMI TIDAK TERCATAT: STUDI KASUS DI DESA MONTORNA PASONGSONGAN SUMENEP - Imam Hafas (Fakultas Agama Islam UNISMA, 2021)
Polygamy is a marriage which exceeds that of a wife, which in this study has a problem against the actions of polygamy was not recorded as well as polygamy is not healthy, where the study focused on the interpretation of Islamic law and positive law against the actions of polygamy such. The coming of the problems of the actions of polygamy in the Village Montorna District Pasongsongan Sumenep originated from the presence of one of the women (widowed) that simply give more attention to that among men in the village. Look at the state of social as well as the status of existing give a little gap as well as the chance of occurrence of polygamy, but the important points in the problems related to the act of polygamy is not recorded is a marriage performed outside the applicable provisions. Of the existing problems can be studied related to basic reasons and factors that the onset of action of polygamy as well as how interpretations of Islamic law and positive law against polygamy is not recorded. This research uses qualitative method with the approach of sociological empirical theoretical as well as primary data source and secondary methods of data collection through observation, interviews and descriptive analysis as a method of data analysis as well as the flow of thinking inductive. The results in this study show that the act of polygamy is not recorded because of the reasons and factors that describe the attitude of the offender are only limited to the desires of lust and selfishness, which the perpetrators never see the will of the welfare as well as the actors who lack understanding of the importance of registration of marriage.